Tyrosination of α‐tubulin controls the initiation of processive dynein–dynactin motility. (11th March 2016) - McKenney, Richard J; Huynh, Walter; Vale, Ronald D; Sirajuddin, Minhajuddin
Abstract: Post‐translational modifications (PTMs) of α/β‐tubulin are believed to regulate interactions with microtubule‐binding proteins. A well‐characterized PTM involves in the removal and re‐ligation of the C‐terminal tyrosine on α‐tubulin, but the purpose of this tyrosination–detyrosination cycle remains elusive. Here, we examined the processive motility of mammalian dynein complexed with dynactin and BicD2 (DDB) on tyrosinated versus detyrosinated microtubules. Motility was decreased ~fourfold on detyrosinated microtubules, constituting the largest effect of a tubulin PTM on motor function observed to date. This preference is mediated by dynactin's microtubule‐binding p150 subunit rather than dynein itself. Interestingly, on a bipartite microtubule consisting of tyrosinated and detyrosinated segments, DDB molecules that initiated movement on tyrosinated tubulin continued moving into the segment composed of detyrosinated tubulin. This result indicates that the α‐tubulin tyrosine facilitates initial motor–tubulin encounters, but is not needed for subsequent motility. Our results reveal a strong effect of the C‐terminal α‐tubulin tyrosine on dynein–dynactin motility and suggest that the tubulin tyrosination cycle could modulate the initiation of dynein‐driven motility in cells. Synopsis: Post‐translational modifications of tubulin can affect motor protein behavior on microtubules. This study reveals that microtubule tyrosination allows for robust initiation of mammalian dynein–dynactin processivity, but that tyrosination is dispensable once dynein is motile. Removal of alpha‐tubulin carboxy‐terminal tyrosine strongly decreases the interaction of the dynein–dynactin complex with microtubules. The dynein–dynactin complex has two separate microtubule binding domains. The CAP‐Gly domain within the dynactin complex senses the tyrosination state of the microtubule and aids in the initiation of processive dynein motility. After the initiation of processive motility, the CAP‐Gly interaction with the microtubule is not required for sustained dynein motility. Abstract : Post‐translational modifications of tubulin can affect motor protein behavior on microtubules. This study reveals that microtubule tyrosination allows for robust initiation of mammalian dynein–dynactin processivity, but that tyrosination is dispensable once dynein is motile.